(-)-Epigallocatechin-3-gallate Ameliorates Intervertebral Disc Degeneration Through Reprogramming of the Circadian Clock - Mei, Liangwei; Zheng, Yi; Ma, Teng; Xia, Bing; Gao, Xue; Hao, Yiming; Luo, Zhuojing; Huang, Jinghui (Frontiers in Pharmacology, 2021)
The circadian clock is vital in the management of our daily physiological as well as metabolic processes. Disturbances of the clock can cause degenerative and age-related diseases. Increasing evidence has indicated that the intervertebral discs contain an internal biological clock related to degeneration. However, to date, no bioactive compounds have been found that can ameliorate intervertebral disc degeneration (IDD) by restoring the circadian clock. (-)-Epigallocatechin-3-gallate (EGCG) is a nutritious food with powerful antioxidant properties, as well as entraining biological clock to improve health. The purpose of this study was to determine whether the protective effects of EGCG on nucleus pulposus (NPCs) under oxidative stress is related to the circadian clock. First, we found that EGCG attenuated H2O2-induced extracellular matrix degradation in NPCs and inhibited H2O2-induced NPC apoptosis. Our in vivo experiments also confirmed this finding. Furthermore, EGCG attenuated H2O2-triggered dampening of phase shifts and daily oscillations in circadian clock gene transcription as well as protein expression levels. Intriguingly, core clock gene (Bmal1) knockdown notably blocked the protective effects of EGCG. To our knowledge, this study provides the first convincing evidence that EGCG prevents IDD in a Bmal1-dependent manner. In general, EGCG supplementation can be used as a nutritional prevention strategy for the rehabilitation of degenerative diseases related to the circadian clock.